Consilience in the Peripheral Sensory Adaptation Response - Wong, Willy (Frontiers in Human Neuroscience, 2021)
Measurements of the peripheral sensory adaptation response were compared to a simple mathematical relationship involving the spontaneous, peak and steady-state activities. This relationship is based on the geometric mean and is found to be obeyed to good approximation in peripheral sensory units showing a sustained response to prolonged stimulation. From an extensive review of past studies, the geometric mean relationship is shown to be independent of modality and is satisfied in a wide range of animal species. The consilience of evidence, from nearly one hundred years of experiments beginning with the work of Edgar Adrian, suggests that this is a fundamental result of neurophysiology.